Exercise-induced metabolomics and its association with metabolic health in adolescents - Xiaoyuan Guo; Zhibo Zhou; Yutong Wang; Huishan Sun; Shanshan Liu; Yiling He; Hanze Du; Hongbo Yang; Huijuan Zhu; Mei Zhang; Bo Ban; Shi Chen; et al. (Nutrition & Metabolism)
Abstract Background While exercise training has been shown to improve various aspects of adolescent metabolic health, such as blood pressure, insulin resistance, and dyslipidemia, the underlying metabolic mechanisms remain poorly understood. No study has examined the metabolomic changes to identify potential mechanisms and explore biomarkers that predict exercise benefits in adolescents. Methods We used propensity score matching to select 54 pairs of adolescents (ages 12–14 years) with and without long-term exercise training. Body mass index (BMI), waist circumference (WC) and metabolic indicators including blood pressure, Homeostasis Model Assessment of Insulin Resistance (HOMA-IR) and triglycerides (TGs) were assessed at enrollment and 1-year follow-up. Untargeted metabolomics was analyzed at enrollment. The associations between metabolites and clinical metabolic indicators were tested. Results Metabolomic analysis revealed 73 differential metabolites between exercise and non-exercise groups, with 59 metabolites associated with metabolic health indicators. Among them, a group of eicosanoids were consistently upregulated and negatively associated with diastolic blood pressure (DBP), HOMA-IR, or TGs, suggesting their potential roles in exercise-related improvements. Receiver operating characteristic analysis showed better predictive performance for exercise benefits on DBP and TGs using papaverine and azelaic acid compared to BMI and WC. Conclusions Adolescents with long-term exercise are associated with improved metabolic health. Metabolomic profiles provide novel insights into the underlying mechanisms and offer useful biomarkers for predicting exercise benefits.